Kadar Albumin dan Bilirubin Penderita Tuberkulosis Paru Pengguna Obat Anti-Tuberkulosis (OAT) Lini-I di Kota Ambon: Sebuah Studi Longitudinal: Albumin and Bilirubin Levels In Pulmonary Tuberculosis Patients Using the First Line Anti-Tuberculosis Drugs in Ambon City: A Longitudinal Study - Elisabeth Grebytha Latuihamallo; Rosdiana Mus; Yanita Novalina Ursula; Vina Latuconsina; Vebiyanti Tentua; Rahmi Latief (Journal of Health, 2026)
Background: Tuberculosis is a global health problem that remains unresolved, including in Indonesia. The high incidence of TB indicates the need for attention in TB control, which is carried out with the Directly Observed Treatment Short Course (DOTS) strategy by supporting patients to take Anti-Tuberculosis Drugs (OAT). TB treatment takes a relatively long time so it is feared that it can cause hepatotoxicity which is diagnosed through albumin and bilirubin levels. Objective: the purpose of this study was to determine the description of albumin and bilirubin levels in patients with pulmonary tuberculosis using OAT in Ambon City. Methods: this study was a descriptive observational study with a prospective cohort approach using purposive sampling technique. The research was conducted in 4 locations, namely at Al-Fatah General Hospital, Tk.II Prof. dr. J. A. Latumeten Hospital, Maluku Province Community Lung Health Center, and Maluku Province Health Laboratory Center. The number of subjects with TB was 21 subjects who met the inclusion criteria, namely patients with pulmonary TB who will undergo first-line OAT treatment. Results: results of this study showed that patients with pulmonary TB were mostly 15-24 years old (33.3%) , male (66.7%), BMI before treatment <18.5 kg/m2 (52.3%), BMI at the end of treatment 18.5-22.9 kg/m2 (57.1%), new cases (90.4%), bacteriologically diagnosed (66.7%), taking Category 1 KDT OAT (100%), and without a history of comorbid diseases (57.2%). Conclusion: During the treatment process, the average albumin level increased within normal limits, while bilirubin levels fluctuated but remained within the normal range.